1999
DOI: 10.2307/3434475
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenic Role for Acetylcholinesterase in Axonal Outgrowth during Neural Development

Abstract: Acetylcholinesterase (AChE) is the enzyme that hydrolyzes the neurotransmitter acetylcholine at cholinergic synapses and neuromuscular junctions. However, results from our laboratory and others indicate that AChE has an extrasynaptic, noncholinergic role during neural development. This article is a review of our findings demonstrating the morphogenic role of AChE, using a neuronal cell culture model. We also discuss how these data suggest that AChE has a cell adhesive function during neural development. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It is described that AChE typically appears during neural development while axons are growing and before synaptic connections form (for review see Layer, 1991). This transient AChE expression is no accident of development, but is correlated with an AChE role of promoting axonal outgrowth or synaptic connection (Anderson and Key, 1999;Bigbee et al, 1999Bigbee et al, , 2000. The present study established that both amacrine cells and ganglion cells were affected by diazinon in their numbers and distribution.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is described that AChE typically appears during neural development while axons are growing and before synaptic connections form (for review see Layer, 1991). This transient AChE expression is no accident of development, but is correlated with an AChE role of promoting axonal outgrowth or synaptic connection (Anderson and Key, 1999;Bigbee et al, 1999Bigbee et al, , 2000. The present study established that both amacrine cells and ganglion cells were affected by diazinon in their numbers and distribution.…”
Section: Discussionsupporting
confidence: 72%
“…All organophosphorus compounds have a mechanism of toxicity in common, that is, phosphorylation of AChE causing accumulation of acetylcholine, overstimulation of cholinergic receptors, and consequently, signs of cholinergic toxicity. On the other hand, organophosphate exposures have also been shown to downregulate muscarinic receptors, inhibit the adenylate cyclase signaling cascade, decrease brain DNA and RNA synthesis, and suppress neurite outgrowth and cell adhesion (Anderson and Key, 1999;Bigbee et al, 1999;Dam et al, 1998;Lein and Fryer, 2005;Li and Casida, 1998;Song et al, 1997). Therefore, developmental exposures may be more dangerous than previously thought, both because acetylcholinesterase may have a direct role on neuronal differentiation, and moreover, the organophosphorus compounds also act on other components of the cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…They do suggest that developmental OP exposure has the potential to disrupt synaptic function, and this disruption is present during the period where we observed behavioral alterations. It has been previously suggested that OP exposure may change neuronal connectivity in the developing brain which could result in aberrant behavioral outcomes (Bigbee et al, 1999;Brimijoin and Koenigsberger, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that developmental neurotoxicity is mediated by mechanisms other than those implicated in acute OP neurotoxicity (Abou-Donia, 2003;Costa, 2006;Ecobichon, 1994). It is postulated that the neurobehavioral deficits associated with developmental CPF exposure reflect altered neuronal connectivity in the developing brain (Bigbee et al, 1999;Brimijoin and Koenigsberger, 1999;Slotkin, 2004a).…”
mentioning
confidence: 99%